2020
DOI: 10.1186/s13045-020-00973-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of BCL2 and FLT3 co-inhibition in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a heterogeneous and complex disease, and treatments for this disease have not been curative for the majority of patients. In younger patients, internal tandem duplication of FLT3 (FLT3-ITD) is a common mutation for which two inhibitors (midostaurin and gilteritinib) with varied potency and specificity for FLT3 are clinically approved. However, the high rate of relapse or failed initial response of AML patients suggests that the addition of a second targeted therapy may be necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…However, clinical experiences with FLT3 inhibitors monotherapy has shown a short duration of response and a high rate of relapse [ 17 , 20 ], suggesting that combination strategies may be needed to improve clinical outcomes. Previous studies have suggested a synergistic effect of BCL-2 inhibition and FLT3 inhibition in preclinical models of FLT3-ITD mutant AML [24] . Therefore, we next sought to investigate the combination of HQP1351 and BCL-2 inhibitor APG-2575 in FLT3-ITD mutant AML models.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, clinical experiences with FLT3 inhibitors monotherapy has shown a short duration of response and a high rate of relapse [ 17 , 20 ], suggesting that combination strategies may be needed to improve clinical outcomes. Previous studies have suggested a synergistic effect of BCL-2 inhibition and FLT3 inhibition in preclinical models of FLT3-ITD mutant AML [24] . Therefore, we next sought to investigate the combination of HQP1351 and BCL-2 inhibitor APG-2575 in FLT3-ITD mutant AML models.…”
Section: Resultsmentioning
confidence: 94%
“…Overexpression of BCL-2 is associated with therapeutic resistance and is a biomarker for worse responses to chemotherapy in patients with AML [21] , [22] , [23] . In an unbiased, large-scale clustered regularly interspaced short palindromic repeats (CRISPR) screening, knockout of BCL-2 enhanced the anti-leukemic effects of FLT3 inhibitors in AML [24] . Venetoclax, a potent and selective BCL-2 inhibitor, has been developed and approved by the FDA in combination with low-dose cytarabine (LDAC) or hypomethylating agents for treatment of elderly patients with AML or those who are ineligible for intensive chemotherapy [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…sustainable CR. One way to improve these results is the simultaneous use of combination of targeted therapy, as illustrated by the synergistic effect of BCL-2 and FLT-3 co-inhibition [ 39 ]. The mechanisms evoked for escape from targeted therapies are obviously multiple, and linked both to the state of the tumor at the beginning of treatment but also to its evolution under treatment, under the possible pressure of targeted therapy +/− conventional chemotherapy +/− adoptive immunotherapy +/− immunity developed by the patient.…”
Section: The Results Obtained By Targeted Therapiesmentioning
confidence: 99%
“…The combination between a FLT3 inhibitor and venetoclax in vitro and in vivo has validated therapeutic effect against various models of FLT3-ITD-driven AML (ref. 37 ). The same technology was used to obtain exportin 1 (XPO1) knockout.…”
Section: Therapeutic Advancesmentioning
confidence: 99%